Salinity Characteristics of Soils Supporting Halophyte Vegetation in Saline Desert Ecosystems in Western India - Mangalassery, Shamsudheen; Dayal, Devi; Patel, Sachin (Annals of Arid Zone, 2018)
Saline soil limits plant growth by affecting osmotic balance in soil-plant systems. Vast areas of saline deserts exist in arid areas of India where crop production is not feasible. One of the ways to effectively utilise such landscape is to use plant species adapted to such hostile environments. Field survey was carried out in two major saline desert ecosystem of western India, namely Great Rann of Kachchh (GRK) and Little Rann of Kachchh (LRK), during 2013 and 2014. The study indicated that these unique ecosystems were deficient in soil organic carbon with content less than 0.77%. Extremes of salinity are common in the study area recording salinity as high as 102.3 dS m-1 in GRK and 85.38 dS m-1 in LRK. The major halophytic plants were Aeluropus lagopoides, Sporobolus marginatus, Suaeda nudiflora and Cressa cretica. Aeluropus was able to grow in soils having salinity upto 27.7 dS m-1, whereas Sporobolus could grow in ecological niches with salinity as high as 83.1 dS m-1. The halophytic non grasses like Suaeda and Cressa were widely distributed in both the saline desert ecosystems. The presence of salts increased the plant population of Suaeda and Cressa up to certain salinity levels. Beyond salinity value of 9.9 dS m-1, the plant density of Suaeda decreased, whereas in Cressa, the salinity value beyond which reduction in population decreased was 27.2 dS m-1. These plants which are able to survive at extremely salinity environments, could be explored for greening saline deserts and could be used as local fodder resource to support livestock population. Key words: Aeluropus lagopoides, Cressa cretica, salinity, soluble ions, Sporobolus marginatus, Suaeda nudiflora.